Implementation Of Agglomerative Clustering Method On Mapping Crime-Prone Areas Of Webgis-Based Lhokseumawe City Case Study Of Lhokseumawe Prosecutor's Office - Teuku Ibrar Faturrahman Ibrar; Safwandi Safwandi; Zahratul Fitri Zahratul Fitri (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The application of the Agglomerative Hierarchical Clustering method was carried out for mapping the Lhokseumawe City area, with a focus on sub-districts grouped by village and their crime rates. The types of crimes analyzed include drugs, oharda (violations of public order and security), and kamtibum (public order and security). The data used came from the Prosecutor's Office and was taken through the Department of Law, covering various crimes that are very detrimental to society. By utilizing Geographic Information System (GIS) technology, this system can provide clear visual information about the location of criminal incidents and the types of crimes that occur in each village. This clustering process allows for the grouping of villages that tend to have high crime rates, thus helping to identify areas that require more attention in law enforcement. The application of this clustering is not new, because previously many researchers and scientists have applied similar methods, but with different case studies. In this context, clustering helps provide more detailed insights into the distribution of crime at the village level, allowing for more focused and targeted prevention efforts.